The Importance and Role of Inclusive Education in Educational Institutions - Akhlan, Riksma Nurahmi Rinalti; Khimmataliyev, Dustnazar Omonovich; Qizi , Omonova Nilufar Parda (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Inclusive education is a state policy aimed at eliminating barriers between disabled and able-bodied children, children with special educational needs, adolescents with disabilities for some reasons, developmental disabilities, or is an educational system that represents inclusion in the general education process aimed at adapting to social life regardless of economic difficulties. Inclusive education ensures that children with special needs receive education on the basis of equal rights with children of normal development. Currently, the education of children with special needs in the system of general education institutions is the main topic that has caused a wide discussion at the world level, and declarations and decisions are being made at the world level. Many countries of the world recognized them. But to date there are many problems in their implementation. In some countries, when laws or decisions on general education are adopted, the issue of education of disabled children is not included in it. But the recognition of inclusive education will not depend only on passing laws. Experiments were conducted in 14 schools in 3 cities of the republic. 114 healthy, 41 disabled students, parents of students, 36 pedagogues were involved. During the research, observation, interview, pictures, tests, and social survey were used.